Old school still matters : lessons from history to reform public education in America - Fife, Brian L. (Santa Barbara, California : Praeger, 2013)
"Can public schools in America be saved? This book considers theory, current practice, and the common school ideal through a historical lens to arrive at practical suggestions for reforming contemporary public education"--
"Please see the text file attached"--
Horace Mann and the common school ideology -- The market-based ideology and politics of the conservative right -- Education and the politics of federalism -- Education and the politics of consumerism and conservatism -- Education in the early twenty-first century -- Citizenship in a republican form of government in the twenty-first century -- Education: a public good worth defending -- Blueprint for progressive reform.
Includes bibliographical references (pages 299-322) and index.
Keywords: Public schools -- United States -- History; Education -- United States -- History; Educational change -- United States -- History; EDUCATION / History; EDUCATION / Educational Policy & Reform / General; Education; Educational change; Public schools; United States; History